The presence of white eggs in the monitoring of Aedes albopictus ( Diptera: Culicidae) by ovitraps. Issue 2 (December 2013) - Drago, Andrea; Martini, Simone; Vettorato, Christian; Pombi, Marco; Dutto, Moreno
ABSTRACT Using international trading and passive transportation routes, the Asian tiger mosquito, Aedes albopictus (Skuse, 1894), has colonized Europe. While the most common tool to monitor the presence of the mosquito is the ovitrap, other kinds of eggs are occasionally found in the traps as well. Most of the eggs are easy to distinguish, however, some white‐yellow eggs have a similar shape and size to those of the tiger mosquito and are often falsely identified as freshly laid tiger mosquito eggs. We have shown that these eggs had been laid by Psychoda alternata Say, 1824, and the misinterpretation may cause large errors in calculating density and patterns of Ae. albopictus. To avoid mistakes, a microscopic observation should be done at least 48 h after collecting the sample to permit Ae. albopictus eggs to darken.